Exploring the molecular tapestry of Sarcodon secondary metabolites: chemical structures, activities, and biosynthesis - Yu-Ying Liu; Ming Zhang; Fei Tang; Hai-Qiang Wang; Jin-Ming Gao; Minglei Li; Jianzhao Qi (Mycology, 2024)
Sarcodon mushrooms are esteemed as a rare and highly valuable resource for both culinary and medicinal purposes. Ancient medical classics have documented their beneficial effects on conditions such as indigestion, loss of appetite, and neurological disorders. Modern phytochemical research into their secondary metabolites has led to the discovery of numerous bioactive compounds with significant biological activities. Despite notable achievements in the study of the chemical composition and bioactivity of Sarcodon mushrooms, a comprehensive understanding of these findings has been lacking. This review provides an exhaustive summary of the advancements in the phytochemistry of Sarcodon mushrooms, as well as the biological and pharmacological activities of the isolated compounds and crude extracts derived from Sarcodon over the past nine decades. A total of 100 secondary metabolites isolated from these mushrooms have been classified into five major categories based on their chemical structures, which exhibit bioactivities such as anti-tumour, neurotrophic, and neuroprotective, antioxidant, anti-inflammatory, antimicrobial, and hypoglycaemic properties. The aim of this study is to establish a scientific foundation for future research in drug discovery, biotechnological development, and the exploration of functional foods involving Sarcodon mushrooms.